Factors associated with institutional delivery service utilization in Ethiopia - Kebede A; Hassen K; Nigussie Teklehaymanot A (Dove Medical Press, 2016)
Alemi Kebede,1 Kalkidan Hassen,2 Aderajew Nigussie Teklehaymanot1 1Department of Population and Family Health, 2College of Health Sciences, Jimma University, Ethiopia Background: Most obstetric complications occur unpredictably during the time of delivery, but they can be prevented with proper medical care in the health facilities. Despite the Ethiopian government’s efforts to expand health service facilities and promote health institution-based delivery service in the country, an estimated 85% of births still take place at home.Objective: The review was conducted with the aim of generating the best evidence on the determinants of institutional delivery service utilization in Ethiopia.Methods: The reviewed studies were accessed through electronic web-based search strategy from PubMed, HINARI, Mendeley reference manager, Cochrane Library for Systematic Reviews, and Google Scholar. Review Manager V5.3 software was used for meta-analysis. Mantel–Haenszel odds ratios (ORs) and their 95% confidence intervals (CIs) were calculated. Heterogeneity of the study was assessed using I2 test.Results: People living in urban areas (OR =13.16, CI =1.24, 3.68), with primary and above educational level of the mother and husband (OR =4.95, CI =2.3, 4. 8, and OR =4.43, CI =1.14, 3.36, respectively), who encountered problems during pregnancy (OR =2.83, CI =4.54, 7.39), and living at a distance <5 km from nearby health facility (OR =2.6, CI =3.33, 6.57) showed significant association with institutional delivery service utilization. Women’s autonomy was not significantly associated with institutional delivery service utilization.Conclusion and recommendation: Distance to health facility and problems during pregnancy were factors positively and significantly associated with institutional delivery service utilization. Promoting couples education beyond primary education regarding the danger signs of pregnancy and benefits of institutional delivery through available communication networks such as health development army and promotion of antenatal care visits and completion of four standard visits by pregnant women were recommended. Keywords: systematic review, Ethiopia, institutional delivery, predictors, associated factors